Published or Perished: Harnessing Consolidated Procurement of National Reference Books - Nurmansyah, Zaidan Fajar; Hariyati, Desy (International Journal of Supply Chain Management, 2021)
The procurement of goods and services is generally carried out in isolation without coordination and integration in the process. Consequently, a number of issues may occur, such as the high number of procurement packages, high administrative cost, and high purchasing cost. Strategies are needed to address those issues, and one potential strategy is consolidated procurement of goods/services. Consolidated procurement has successfully been carried out by the Government of Indonesia through the National Public Procurement Agency (LKPP) for the procurement of national textbooks for the primary, junior high, and senior high schools. This paper reports on the implementation, challenges, and benefits at every stage of the consolidated procurement of the national textbooks in Indonesia.This study employed a qualitative approach and method by interviewing informants selected through purposive sampling. The informants in this research came from the Ministry of Education and Culture, the National Public Procurement Agency (LKPP), and book publishers as procurement vendors. Data analysis was conducted through open, selective, and axial coding whereby data from different informants were triangulated. The findings suggested that the consolidated procurement of the national textbooks, which was conducted in three phases, namely planning, tendering, and contract delivery, involved several strategies and faced a number of challenges. Studies on and practice of consolidated procurement of goods/services in Indonesia remain limited. Therefore, this article is expected to serve as a reference for future studies and for practitioners/government who wish to conduct consolidated procurement. Keywords— Consolidated procurement, Challange of consolidated procurement, Advantage of consolidated procurement, national textbooks, procurement of goods/services in Indonesia,